2022
DOI: 10.26444/aaem/147297
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiota of berry fruits – levels of filamentous fungi and mycotoxins, composition of fungi, and analysis of potential health risk for consumers

Abstract: Introduction and Objective.The aim of the study was to determine the presence, concentration and generic composition of filamentous fungi. Selected mycotoxins were also determined: total aflatoxins and deoxynivalenol. Materials and method. In 2017-2018, 40 samples of strawberry fruits and 40 samples of red raspberry fruits were collected. In 2019-2020, 37 samples of fresh strawberry fruits and 41 samples of fresh red raspberry fruits were collected on conventional farms located in eastern Poland and were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…We should note that one of 40 analyzed strawberry samples contained 13 MTs including AFL В1 and ОТА (6.55 µg/kg, which was higher than the hygienic standard established for OTA in other types of plant products) as well as several fusariotoxins including DON and FВ1+FВ2 (98.09 µg/kg and 66.00 µg/kg accordingly), MPA and CIT (in trace quantities). AFL contamination in strawberries was also reported by T. Klapec et al, 2022, who identified several AFL (except AFL В1) in 70 % of the analyzed samples; the maximum contamination level reached 3.185 µg/kg [19].…”
Section: T a B L E 1 Mt Detection Parameters For Hplc-ms/mssupporting
confidence: 76%
“…We should note that one of 40 analyzed strawberry samples contained 13 MTs including AFL В1 and ОТА (6.55 µg/kg, which was higher than the hygienic standard established for OTA in other types of plant products) as well as several fusariotoxins including DON and FВ1+FВ2 (98.09 µg/kg and 66.00 µg/kg accordingly), MPA and CIT (in trace quantities). AFL contamination in strawberries was also reported by T. Klapec et al, 2022, who identified several AFL (except AFL В1) in 70 % of the analyzed samples; the maximum contamination level reached 3.185 µg/kg [19].…”
Section: T a B L E 1 Mt Detection Parameters For Hplc-ms/mssupporting
confidence: 76%
“…Moreover, microscopic observations carried out on the fruit that showed decay revealed the presence of different fungal genera such as Alternaria, Cladosporium, Botrytis, Epicoccum, Colletotrichum, Mucor, and Penicillium. Some of these genera included many mycotoxigenic species, as reported elsewhere [62], and, for this reason, post-harvest treatment with chitosan is important to reduce the fungal inoculum present on the raspberry fruit.…”
Section: Fungal Decay On Treated and Untreated Raspberriesmentioning
confidence: 62%
“…A mutant collection of 3800 M2 families was produced using MUC-16 as the WT and EMS as the mutant agent. According to consistent mutant phenotyping, mutations that affected ET sensitivity impacted seedling germination, sex determination, sex expression parthenocarpy, and fruit set [121]. ET affects zucchini sensitivity to chilling damage (CI), with more resistant varieties producing less ET when exposed to low temperatures.…”
Section: Bothmentioning
confidence: 99%